1998
DOI: 10.1021/om970876n
|View full text |Cite
|
Sign up to set email alerts
|

Chlorosilyl-Substituted Monocyclopentadienyl Niobium Chloro, Imido Chloro, and Benzyl Complexes. X-ray Molecular Structure of [{(NbCl2)2(μ-O)(μ-Cl)2}{(η5-C5H4)2(Me2SiOSiMe2)}]

Abstract: We report the synthesis of 1-(chloromethylphenylsilyl)cyclopentadiene. The reaction of a toluene/CH 2 Cl 2 suspension of NbCl 5 with 1-(SiClMeX)-1-(SiMe 3 )C 5 H 4 (X ) Me, Ph) leads to the monocyclopentadienyl derivatives [M{η 5 -C 5 H 4 (SiClMeX)}Cl 4 ] (X ) Me, Ph) in 90 and 78% yields, respectively. Reaction of 1 equiv of water with [M{η 5 -C 5 H 4 (SiClMe 2 )}Cl 4 ] in toluene takes place with elimination of HCl, resulting in formation of the dinuclear niobium oxo derivative [{(NbCl 2 ) 2 (µ-O)(µ-Cl) 2 }{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…The selective hydrolysis of the Si-Cl bond with formation of a Si-O-Si bridge was the expected behaviour for this type of niobium compound [11,27]. In contrast, it was observed [6,[30][31][32][33] that the hydrolysis reactions of related monocyclopentadienyl group 4 metal complexes with Scheme 1. the chloro-silylcyclopentadienyl ligand afforded Si-O-M bridges.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The selective hydrolysis of the Si-Cl bond with formation of a Si-O-Si bridge was the expected behaviour for this type of niobium compound [11,27]. In contrast, it was observed [6,[30][31][32][33] that the hydrolysis reactions of related monocyclopentadienyl group 4 metal complexes with Scheme 1. the chloro-silylcyclopentadienyl ligand afforded Si-O-M bridges.…”
Section: Resultsmentioning
confidence: 88%
“…It has been suggested that aryl-imido ligands provide more crystalline solids [26]. Consequently, we decided to extend our research on Si-Cl functionalized monocyclopentadienyl niobium complexes [11,27,28] to isolate new aryl-imido derivatives using the organomagnesium compounds [Mg(NAr)-(THF)] 6 (Ar = 2,6-Me 2 C 6 H 3 , 1a; Ph, 1b) as imido transfer reagents. This method was first published by Power and co-workers [29] to obtain titanium and zirconium imido compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes 1-3 present three nucleophilic centers that can react with protic acids: the Nb-Cl, [21][22][23][24] the Nb-C [24] , and the oxametallacyclic Nb-O [19] bonds. It would be reasonable to expect that the Nb-C bond should be the most reactive one toward protonolysis due to its lower bond energy, the higher energy of the resulting C-H bond, and the higher nucleophilic character of the niobium-bonded alkyl carbon atom.…”
Section: X-ray Structure Of 1a 2a and 2cmentioning
confidence: 99%
“…We focused our research interest on studies related to cyclopentadienyl group 4-6 metal complexes supporting modified cyclopentadienyl rings [2][3][4][5][6][7][8][18][19][20][21][22][23][24], and reported the synthesis of silyl-g-amido cyclopentadienyl group 4 and 5 metal complexes using the related (chlorodimethylsilyl)cyclopentadienyl metal derivatives [2][3][4][5][6][7][8]24]. Hydrolysis of these compounds also led to the isolation of dinuclear derivatives with Si-O-Si bridges for Nb [8,21,25], Mo and W [24] and Si-O-M bridges for Nb [25] and group 4 metals [2,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of these compounds also led to the isolation of dinuclear derivatives with Si-O-Si bridges for Nb [8,21,25], Mo and W [24] and Si-O-M bridges for Nb [25] and group 4 metals [2,26,27].…”
Section: Introductionmentioning
confidence: 99%